Genealogies of Mahāyāna Buddhism: emptiness, power and the question of origin - Walser, Joseph (Routledge, 2018)
Cover; Title; Copyright; Dedication; Contents; Acknowledgements; Part I Genealogies of Mahāyāna; 1 Introduction: on origins and genealogies; 2 Mahāyāna in retrospect: from my house to the Dalai Lama (looking back from 2017 to 1930); Assessing the essence; Tibet as Buddhist: tracing the lines of power; Emptiness and the analytic of power; Inculcating dispositions to authority: the Kālacakra; 3 Mahāyāna in the republic, Mahāyāna in the empire: tracing "religion" from republican China to the early Qing Dynasty (1920s -- 1723); Religion vs. superstition in 20th-century East Asia